Instrumen State-Trait Anxiety Inventory–Trait (STAI-T) Mengukur Kecemasan Pada Pasien Kemoterapi - Pratiwi, Chaterina Janes; Ningsih, Arum Dwi (MAHESA : Malahayati Health Student Journal, 2022)
ABSTRACT Nursing diagnosis for psychosocial problems that is often complained by chemotherapy patients is anxiety. Anxiety in cancer patients is often not identified in oncology nursing care, especially at the beginning of patients undergoing chemotherapy. The aim to know the effectiveness of State-Trait Anxiety Inventory-Trait (STAI-T) instrument in measuring the anxiety level of patients undergoing chemotherapy. A total of 33 chemotherapy patients were involved in this study. Based on the assessment with open-ended questions, it was found that 14 patients had no complaints of anxiety, 17 patients had mild anxiety, and 2 patients had moderate anxiety. However, with STAI-T instrument, different results were obtained from open-ended questions, 11 patients had mild anxiety, 15 patients had moderate anxiety and 6 patients had severe anxiety. Conclusion : STAI-T instrument that can measure the anxiety levels with better sensitivity than open-ended questions for patients undergoing chemotherapy. Keywords: Anxiety, STAI-T, Chemotherapy ABSTRAK Masalah keperawatan psikososial yang sering dikeluhkan pasien kemoterapi adalah cemas. Cemas pada pasien kanker sering tidak teridentifikasi dalam pelayanan keperawatan onkologi terutama diawal pasien menjalani kemoterapi. Tujuan mengimplementasikan instrumen State-Trait Anxiety Inventory–Trait (STAI-T) dalam mengukur tingkat cemas pasien kemoterapi. Sebanyak  33 pasien kemoterapi terlibat dalam penelitian ini. Berdasarkan pengkajian dengan pertanyaan terbuka didapatkan hasil 14 pasien tidak ada keluhan cemas, 17 pasien cemas ringan, dan 2 pasien cemas sedang. Namun dengan STAI-T didapatkan hasil yang berbeda dengan pertanyaan terbuka yaitu 11 pasien cemas ringan, 15 pasien cemas sedang dan 6 pasien cemas berat. Kesimpulan STAI-T merupakan instrumen yang dapat mengukur tingkat cemas pasien kemoterapi dibandingkan pertanyaan terbuka. Kata kunci: Cemas, STAI-T, Kemoterapi